INVESTIGATE THE RELATIONSHIP BETWEEN RISK AND SIZE OF THE PORTFOLIO IN IRANIAN INSURANCE COMPANIES: Life Sciences-Management - PEYMAN RANJBAR; SAFYAR AMINI (International Journal of Life Science and Pharma Research, 2022)
The aim of this study was to investigate the relationship between insurance risk portfolio and the portfolio is located in Tehran Stock Exchange. The population of this research firms with the insurance activity is located in the Stock Exchange that its financial statements have been audited and the time period is from 2006 to 2015.To test the hypothesis of linear regression models were used to evaluate the method for mixed data (panel data). The results show that the risk of increased portfolio size and the range includes 24 to 36 of the basket good portfolio.